THE FIRE RESISTANCE OF CONCRETE MADE WITH RECYCLED PLASTIC AS PARTIAL REPLACEMENT FOR COARSE AGGREGATE (Malaysian Journal of Civil Engineering, 2022)
This research is aimed to investigate the fire resistance of recycled discarded plastic when used as partial replacement for normal granite coarse aggregate in concrete when exposed to elevated temperatures. Discarded Polyethylene Terephthalate (PET) bottles were cut into a maximum size of 20mm to produce Recycled Plastic Aggregate (RPA). The replacement of normal aggregates with RPA were in proportion of 0%, 5%, 10%, 15%, 20%, 25% and 30% by weight of normal coarse aggregate. The compressive performance of the concrete made with RPA were studied by casting three 100 mm cubes for each of the percentage replacements and tested at 7, 14 and 28 days of curing age. A set of three (3) concrete cubes for each percentage replacement was cured for 28 days and subjected to a temperature of 718oC for a duration of 15 minutes in a furnace. Results of slump tests on fresh concrete showed that workability decreased with increase in RPA. Densities and compressive strengths for normal cube samples not subjected to elevated temperatures and the sample subjected to temperature of 718oC increased with increase in curing age and decreased with increase in percentage of RPA. The result showed that the concrete specimen with 10% replacement of RPA was optimum for good thermal stability.